KLASIFIKASI PENGGUNAAN LAHAN DI HUTAN KEMASYRAKATAN KESATUAN PENGELOLAAN HUTAN LINDUNG MODEL UNIT XIV TOBA SAMOSIR - Dea Kartika Br Pinem; Rahmawaty Rahmawaty; Abdul Rauf (Program studi Kehutanan USU, 2016)
Toba Samosir Forest Management Unit has a Community Forest (HKm) managed by Farmers Group Association Sibisa Motung. This study aimed to classify land use in community Forest at Toba Samosir Forest Management Unit. The research was conducted from April to May 2015 using the Stratified Random Sampling method. The results showed that there are six land use system in HKm, that is the type of combination of forest trees and perennial plants (PlPhTh), the type of combination of forest trees, perennial plants and vegetable plants (PlPhThTs), the type of combination of forest trees, perennial plants and fruit plants (PlPhTtPb), the type of combination of forest trees, vegetable plants and fruit plants (PlPhTsPb), the type of combination of forest trees and vegetable plants (PlTtPb), type of forest trees, perennial plans, vegetable plants and fruit plants (PlPhTtTsPb) and spread in village Motung, village Pardamean Sibisa and village Sigapiton. Combination type of forest trees, perennial plans, vegetable plants and fruit plants are either applied for maximing farmland and provide economic benefits for farmers. Keywords: Land Use Classification, Community forest, Forest Management Unit, Toba Samosir,